A Microbe Associated with Sleep Revealed by a Novel Systems Genetic Analysis of the Microbiome in Collaborative Cross Mice. Issue 3 (1st March 2020) - Bubier, Jason A; Philip, Vivek M; Quince, Christopher; Campbell, James; Zhou, Yanjiao; Vishnivetskaya, Tatiana; Duvvuru, Suman; Blair, Rachel Hageman; Ndukum, Juliet; Donohue, Kevin D; Foster, Carmen M; Mellert, David J; et al.
Abstract: Host genetic diversity provides a variable selection environment and physiological context for microbiota and their interaction with host physiology. Using a highly diverse mouse population, Bubier et al. identified that Odoribacter abundance influences sleep archi-tecture in a manner... The microbiome influences health and disease through complex networks of host genetics, genomics, microbes, and environment. Identifying the mechanisms of these interactions has remained challenging. Systems genetics in laboratory mice ( Mus musculus ) enables data-driven discovery of biological network components and mechanisms of host–microbial interactions underlying disease phenotypes. To examine the interplay among the whole host genome, transcriptome, and microbiome, we mapped QTL and correlated the abundance of cecal messenger RNA, luminal microflora, physiology, and behavior in a highly diverse Collaborative Cross breeding population. One such relationship, regulated by a variant on chromosome 7, was the association of Odoribacter (Bacteroidales) abundance and sleep phenotypes. In a test of this association in the BKS.Cg- Dock7 m +/+ Lepr db / J mouse model of obesity and diabetes, known to have abnormal sleep and colonization by Odoribacter, treatment with antibiotics altered sleep in a genotype-dependent fashion. The many other relationships extracted from this study can be used to interrogate other diseases, microbes, and mechanisms.